2009
DOI: 10.1113/jphysiol.2009.171082
|View full text |Cite
|
Sign up to set email alerts
|

Whither the hypercolumn?

Abstract: Among the crowning achievements of Hubel and Wiesel's highly influential studies on primary visual cortex is the description of the cortical hypercolumn, a set of cortical columns with functional properties spanning a particular parameter space. This fundamental concept laid the groundwork for the notion of a modular sensory cortex, canonical cortical circuits and an understanding of visual field coverage beyond simple retinotopy. Surprisingly, the search for and description of analogous hypercolumnar organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 56 publications
(92 reference statements)
4
47
0
2
Order By: Relevance
“…functional domains for disparity are located in V2 thick stripes (Livingstone and Hubel, 1988;Ts'o et al, 2001Ts'o et al, , 2009Chen et al, 2008), where direction-selective domains were also found (Figs. 2 E, 8).…”
Section: The Possible Functional Role For V2 Direction Domainsmentioning
confidence: 81%
See 1 more Smart Citation
“…functional domains for disparity are located in V2 thick stripes (Livingstone and Hubel, 1988;Ts'o et al, 2001Ts'o et al, , 2009Chen et al, 2008), where direction-selective domains were also found (Figs. 2 E, 8).…”
Section: The Possible Functional Role For V2 Direction Domainsmentioning
confidence: 81%
“…Drifting sine-wave gratings are the most popular visual stimuli used to map cortical orientation domains (Grinvald et al, 1986;Ts'o et al, 1990;Blasdel, 1992;Khaytin et al, 2008;Ts'o et al, 2009;Lu et al, 2010;Pan et al, 2012), whereas stimuli such as visual noise and dots are widely used to dissect the motion processing system (Mackay, 1965;Nakayama and Tyler, 1981;Britten et al, 1992;Snowden et al, 1992). In this study, to maximally remove non-motion related cues, we employed lowpass filtered FNS, whose global translation was varied only in the direction, speed, and axis of motion.…”
Section: Resultsmentioning
confidence: 99%
“…However, classification in V2 is complicated by the presence of domains within the thin stripes sensitive to low spatial frequency temporal luminance modulations (Wang et al, 2007). In addition, despite the apparently larger spatial extent of the stripes compared to the V1 blobs, careful analysis shows that the spatial periodicity of the V1 and V2 color domains is very similar (Ts’o et al, 2009). It is not clear, therefore, that classification performance in V2 should surpass that in V1.…”
Section: Discussionmentioning
confidence: 99%
“…For example, whereas primary visual cortex (V1) inherits a basic retinotopic organization, additional maps of orientation, spatial frequency, ocular dominance, and other higher-order attributes of the visual scene also are embedded into its cortical architecture [17, 38]. Decorrelation and related tuning operations in V1 are performed with respect to higher-order visual stimulus attributes rather than retinotopy per se – e.g., the regulation of orientation selectivity [89].…”
Section: Computations In the External Plexiform Layermentioning
confidence: 99%